2010
DOI: 10.1017/s0022112009992965
|View full text |Cite
|
Sign up to set email alerts
|

Large-eddy simulation of mixing in a recirculating shear flow

Abstract: The flow field and mixing in an expansion-ramp geometry is studied using large-eddy simulation (LES) with subgrid scale (SGS) modelling. The expansion-ramp geometry was developed to investigate enhanced mixing and flameholding characteristics while maintaining low total-pressure losses. Passive mixing was considered without taking into account the effects of chemical reactions and heat release, an approximation that is adequate for experiments conducted in parallel. The primary objective of the current work is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…The resulting LES solutions are distinctive in the sense that the solution is always underresolved, meaning that flow fields always exhibit significant fluctuations at scales close to the grid resolution. Accordingly, increasing the grid resolution does not make the LES solution ''smoother'' and any advantages gained are because of improvements in the performance of the SGS model (e.g., Pope 2004;Matheou et al 2010). As a consequence, when finite differences are used to discretize the differential operators, the formal order of accuracy of the approximation is inconsequential and what is relevant in LES is the dispersion characteristics, as shown in the seminal work of Ghosal (1996Ghosal ( , 1999.…”
Section: Discrete Modelmentioning
confidence: 99%
“…The resulting LES solutions are distinctive in the sense that the solution is always underresolved, meaning that flow fields always exhibit significant fluctuations at scales close to the grid resolution. Accordingly, increasing the grid resolution does not make the LES solution ''smoother'' and any advantages gained are because of improvements in the performance of the SGS model (e.g., Pope 2004;Matheou et al 2010). As a consequence, when finite differences are used to discretize the differential operators, the formal order of accuracy of the approximation is inconsequential and what is relevant in LES is the dispersion characteristics, as shown in the seminal work of Ghosal (1996Ghosal ( , 1999.…”
Section: Discrete Modelmentioning
confidence: 99%
“…Similar to the treatment in Matheou et al (2010), we have calculated the SGS-TKE using the data in case 3 and identified that the ratio of the SGS-TKE to the total TKE is less than 20 %, indicating a sufficiently resolved LES resolution (Pope 2004;Ferrante, Matheou & Dimotakis 2011). Moreover, the Kolmogorov scale η is also estimated as η/D ∼ O(10 −4 ) and the grid spacing in the shear layer region is δ/D ∼ O(10 −3 ).…”
Section: Validationmentioning
confidence: 71%
“…Then, the ratio δ/η is O(10). Compared to the LES of a mixing layer with δ/η ∼ O(10 2 ) (Matheou et al 2010), it is verified that the grid resolution is sufficient to resolve turbulence in the flow field. Thus, the quality of the present simulation is capable of capturing meaningful turbulence.…”
Section: Validationmentioning
confidence: 92%
“…LES takes a different approach by resolving the larger scales while modeling the smaller scales. While LES of unbounded homogeneous and shear turbulence is well established (e.g., Misra and Pullin, 1 Ferrante et al, 2 Pitsch, 3 Matheou et al, 4 and Foysi and Sarkar 5 ), LES of wall bounded flows has remained challenging, first, because the existence a) namiko@caltech.edu. of a wall causes the length scales to be progressively smaller towards the wall, and second, owing to near-wall anisotropy.…”
Section: Introductionmentioning
confidence: 99%